A clinicopathological study of oral premalignant and malignant lesions with a special focus on gingivobuccal complex in a tertiary care center - Rashmi Rekha Mahapatra; Rupa Das; Kalyani Prava Gouda; KCKDN Hembram; Tribikram Debata; Manas Ranjan Satpathy (Asian Journal of Medical Sciences, 2023)
Background: Globally, oral cavity lesions are a serious public health issue. Premalignant lesions of the oral cavity, such as leukoplakia, erythroplakia, and oral submucous fibrosis, are common in India and are strongly associated with tobacco and betel nut use. These lesions have the potential to transform into malignancies, with squamous cell carcinoma (SCC) being the predominant type of oral cancer. Early detection and effective management of early malignant lesions are crucial to improving the prognosis for patients. Histopathological examination is a standard procedure used to identify these lesions.